1977
DOI: 10.1071/bi9770345
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Fusion of the TOL Plasmid with the R91 Drug Resistance Plasmid in Pseudomonas aeruginosa

Abstract: The TOL catabolic plasmid was shown to be compatible with the R91 drug resistance plasmid. However, the TOL plasmid was extremely unstable in mutant PA03 of P. aeruginosa. By selecting for stabilization of the TOL plasmid in PA03 harbouring R91, it was possible to isolate a strain in which markers from both R91 and TOL appeared to exist in a single recombinant plasmid. This plasmid, pND3, encoded resistance to carbenicillin, was able to transfer at the same frequency as the R91 plasmid and encoded the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The concatamerization of multiple drug resistance genes on a single episomal element is thought to occur through a stepwise fusion of multiple resistance plasmids. Similar fusion events have been found to occur for of R factors and TOL plasmids, the latter of which carry genes essential for the catabolism of small aromatic compounds present in soil (336). The second mechanism by which a single genetic event can result in resistance to multiple drugs is the acquisition of genes encoding drug efflux pumps (179).…”
Section: Mechanisms Of Antibiotic Resistancementioning
confidence: 88%
“…The concatamerization of multiple drug resistance genes on a single episomal element is thought to occur through a stepwise fusion of multiple resistance plasmids. Similar fusion events have been found to occur for of R factors and TOL plasmids, the latter of which carry genes essential for the catabolism of small aromatic compounds present in soil (336). The second mechanism by which a single genetic event can result in resistance to multiple drugs is the acquisition of genes encoding drug efflux pumps (179).…”
Section: Mechanisms Of Antibiotic Resistancementioning
confidence: 88%
“…--2-2-0 become integrated into an R plasmid without any detectable chromosome-linked intermediate (22,33).…”
Section: Methodsmentioning
confidence: 99%
“…Several workers have reported the isolation of hybrid plasmids between the TOL plasmid pWWO and various R plasmids (4,16,19,20,32), and it has been suggested that the TOL genes may be carried on a transposonlike element. However, Lehrbach et al (13) showed by restriction endonuclease analysis that the amount of TOL DNA present in the hybrid plasmids varied from 56 to 104 kilobases (kb), and thus it is clear that transposition of a unique DNA segment from the TOL plasmid cannot be responsible for hybrid formation.…”
mentioning
confidence: 99%